An Evaluation study of the preparatory year experience For medical faculties at Tishreen University from the point of view of the parents - أيوب رنيم; رامي أمون (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of the current research is to investigate the reality of the preparatory year for medical faculties at Tishreen University from the point of view of the parents in term of the degree of satisfaction that the son is currently studying, and the triage system at the end of the preparatory year. In addition to monitor the reality of students orientation to private institutes, The method was used descriptive, and the tool was a questionnaire, which was applied to (100) parents of students who have passed the preparatory year experience. The results of the research confirmed that the highest percentage of parents 82% are satisfied with the current specialty that the son/ daughter is studding. 67% of the parents confirmed that their children have undergone courses outside the university because of the enormity of the curriculum, and the huge numbers of students in the college stands, and being a fateful year. While the higher percentage of parents 59% are satisfied with the sorting method to a good degree. They confirmed that their children were subjected to psychological pressure throughout the school year. Convergence of proportions between supporters. The percentage of those who support and reject the preservation of the preparatory year have also converges. While retaining the preparatory while a small percentage with its cancellation.